Consolidating or Non-consolidating Queues: A Game Theoretic Queuing Model with Holding Costs - WEE, Kwan Eng (Institutional Knowledge at Singapore Management University, 2011)
We consider a two-server queueing system in which the servers choose their service rate based on the demand and holding cost allocation scheme offered by the demand generating entity. We provide an optimal holding cost allocation scheme that leads to the maximum possible service rate for each of a pooled and a split system. Our results suggest that careful allocation of holding costs can create incentives that enable minimum turnaround times using a common queue.